2021
DOI: 10.1002/agj2.20747
|View full text |Cite
|
Sign up to set email alerts
|

Seed coating by biofertilizer containing spores of Bacillus pumilus TUAT1 strain enhanced initial growth of Oryza sativa L. 

Abstract: In rice production, early growth is often slow in direct‐seeded system. Techniques to overcome this barrier are needed. This study evaluated the effectiveness of Kikuichi—a biofertilizer containing Bacillus pumilus TUAT1 spore—in promoting rice growth in a direct‐sowing system. Oxygen, iron, and molybdenum as coating materials were also evaluated to combine with biofertilizer. The seeds were coated with powdered Kikuichi with polyvinyl alcohol followed by a coating with calcium peroxide (CALPER), molybdenum (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…Further investigation using tagged bacteria will help to track CDB in a complex soil environment and understand the mechanism underlying their low survivability in high calcium soils. Alternatively, CDB may be applied via other methods such as a seed coating or even an in-furrow spray (Malusáet al, 2012;Herrmann and Lesueur, 2013;Ma, 2019;Agake et al, 2021). One of the greatest threats to peanut production is the increased presence of A. flavus and its potential to produce the mycotoxin aflatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation using tagged bacteria will help to track CDB in a complex soil environment and understand the mechanism underlying their low survivability in high calcium soils. Alternatively, CDB may be applied via other methods such as a seed coating or even an in-furrow spray (Malusáet al, 2012;Herrmann and Lesueur, 2013;Ma, 2019;Agake et al, 2021). One of the greatest threats to peanut production is the increased presence of A. flavus and its potential to produce the mycotoxin aflatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Agake et al reported a double coating seed treatment to enhance early growth in directseeded rice cultivation. 60 The seeds were first coated with a PVA layer inoculated with a biofertilizer following which a second layer consisting of commercial coating materials was applied. Materials investigated for the secondary layer 2) seeds coated with only layer 1 (L1), (3) bi-layer coated seeds (L2).…”
Section: Multilayered Seed Coatingsmentioning
confidence: 99%
“…Benmoly double coating significantly increased growth as per Tukey's test (P ≤ 0.05). Figure adapted with permission 60. Copyright Wiley 2021.…”
mentioning
confidence: 99%
“…The nutrient supplies of plants are significantly influenced by microorganisms such as bacteria and fungi [ 1 , 2 , 3 , 4 ]. Those microorganisms that have a positive effect and stimulate plant growth are defined as plant growth-promoting (PGP) microorganisms [ 5 , 6 , 7 ], including those that form spores.…”
Section: Introductionmentioning
confidence: 99%